Component resolved diagnostics for hymenoptera venom allergy. Issue 5 (October 2017) - Jakob, Thilo; Müller, Ulrich; Helbling, Arthur; Spillner, Edzard
Abstract : Purpose of review: Component-resolved diagnostics makes use of defined allergen molecules to analyse IgE-mediated sensitizations at a molecular level. Here, we review recent studies on the use of component-resolved diagnostics in the field of Hymenoptera venom allergy (HVA) and discuss its benefits and limitations. Recent findings: Component resolution in HVA has moved from single molecules to panels of allergens. Detection of specific immunoglobulin E (sIgE) to marker and cross-reactive venom allergens has been reported to facilitate the discrimination between primary sensitization and cross-reactivity and thus, to provide a better rationale for prescribing venom immunotherapy (VIT), particularly in patients sensitized to both honeybee and vespid venom. Characterization of IgE reactivity to a broad panel of venom allergens has allowed the identification of different sensitization profiles that in honeybee venom allergy were associated with increased risks for side effects or treatment failure of VIT. In contrast, component resolution so far has failed to provide reliable markers for the discrimination of sensitizations to venoms of different members of Vespidae. Summary: Component-resolved diagnostics allows a better understanding of the complexity of sensitization and cross-reactivities in HVA. In addition, the enhanced resolution and precision may allow identification of biomarkers, which can be used for risk stratification in VIT. Knowledge about the molecular composition of different therapeutic preparations may enable the selection of appropriate preparations for VIT according to individual sensitization profiles, an approach consistent with the goals of personalized medicine.